The Golem of Hollywood [large type] - Kellerman, Jonathan; Kellerman, Jesse (Thorndike Press, a part of Gale, Cengage Learning, 2014)
The legend of the Golem of Prague has endured through the ages: a creature fashioned by a sixteenth-century rabbi to protect his congregation, now lying dormant in the garret of a synagogue. But the Golem is dormant no longer.... Detective Jacob Lev has been assigned to a Special Projects squad he didn't even know existed, and sent to a murder scene far up in the hills of Hollywood Division. There is no body, only an unidentified head lying on the floor of a house. Seared into a kitchen counter nearby is a single word: the Hebrew for justice.